Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Barrientos Rodriguez, Carlos Leoncio (2019)
This document intends to perform an analysis and diagnosis of the company, Camposol, and the Peruvian agribusiness sector. Also, propose a strategic plan. The performed analysis, through strategic management models (Canvas model, value chain, PEST analysis and Porter’s five forces) allowed us to understand the context of Camposol, both internally and externally. Then, strategies are established that take advantage or should take advantage of the aforementioned factors and be able to achieve the strategic objectives set, through quantitative matrices of strategic planning. Then, for the implementation of the strategies, the redefinition of the organizational structure and strategic proposals for improvement within the organization and strategies were proposed, with the purpose of guiding the organization towards the strategic objectives in the most efficient way and compliance thereof. To control and monitor compliance with the objectives, a comprehensive scorecard is proposed, with the use of the Balanced Scorecard model and strategic indicators.